Pembelajaran Organ Tubuh Manusia Menggunakan Aplikasi Berbasis Android - Sunaryono; Wika Purbasari; Dewi Erla Mahmudah; Anisa Septiani Suroso (Jurnal Pendidikan dan Pengajaran, 2023)
Along with the rapid development of technology, the current learning procces still tends to use manualization. So we need other alternatives that are interactive and not boring. This application was build using prototyping methods with stages, needs identification, prototyping development, interviews, returns and enhancements. The result of testing the product test produced a value of 83,79 % above the specivied value of 75 %, while the benefit test obtained a result of 92,912 % above the specified value of 75 % with the highest result of the learnability criteria. The result of this study can procces learning faster than the manual method and can be operated properly by the user. So than this application is expected to facilitate and support learning so student can be interested in the material presented.